Noninvasive Tests to Assess Fibrosis and Disease Severity in Metabolic Dysfunction-Associated Steatotic Liver Disease - Tincopa, Monica A.; Loomba, Rohit (Seminars in Liver Disease, 2024)
Risk of disease progression and clinical outcomes in metabolic dysfunction-associated steatotic liver disease (MASLD) is associated with fibrosis stage and presence of “at-risk metabolic dysfunction-associated steatohepatitis (MASH).” Although liver biopsy is considered the gold standard to diagnose MASH and stage of fibrosis, biopsy is infrequently performed in clinical practice and has associated sampling error, lack of interrater reliability, and risk for procedural complications. Noninvasive tests (NITs) are routinely used in clinical practice for risk stratification of patients with MASLD. Several NITs are being developed for detecting “at-risk MASH” and cirrhosis. Clinical care guidelines apply NITs to identify patients needing subspecialty referral. With recently approved Food and Drug Administration treatment for MASH and additional emerging pharmacotherapy, NITs will identify patients who will most benefit from treatment, monitor treatment response, and assess risk for long-term clinical outcomes. In this review, we examine the performance of NITs to detect “at-risk MASH,” fibrosis stage, response to treatment, and risk of clinical outcomes in MASLD and MASH.
Keywords: NAFLD; MASLD; MASH; noninvasive tests